REKOMENDASI CALON KARYAWAN MENGGUNAKAN FUZZY INFERENCE SYSTEM PADA SISTEM REKRUTMEN PT. SEMANGAT SEJAHTERA BERSAMA - Margaret Anggarwati (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Recommended Employee Candidate with Fuzzy Inference System for Recruitmen System at PT Semangat Sejahtera Bersama is a website application that can connect between applicants (job seekers) and companies (employers). Applicants can find information about job vacancy available. Recommended Employee Candidate Applications created using Fuzzy Inference System to process recommendation applicants. Fuzzy Inference System Mamdani can give applicants recommendation in accordance with the prescribed criteria. Based on test results, it is known that the determination of the value of between criteria influence on the final result. The testing process was conducted on 20 samples from the company and another 10 random samples. The test results are corresponding with what the company want, from the result the 2 applicant that’s not chosen got the lowest point from the system output.